A DNA microarray for the versatile diagnosis of infectious diarrhea. Issue 7 (12th June 2013) - Donatin, Emilie; Buffet, Sylvain; Leroy, Quentin; Raoult, Didier; Drancourt, Michel
<x xml:space="preserve">Abstract</x> Several bacteria, viruses, and parasites cause diarrhea as coinfecting pathogens. We designed a DNA microarray comprising 60‐bp probes spotted 194 times for the multiplex detection of 33 enteropathogenic bacteria and seven enteropathogenic viruses, and the archaeon Methanobrevibacter smithii was used as an internal positive control. Nine pathogen‐free stool specimens were used as negative controls. One of these control specimens was further spiked with Salmonella enterica as a positive control. The microarray was then tested with 40 pathological stool specimens, comprising S. enterica (n = 30), Campylobacter jejuni (n = 4), pathogenic Escherichia coli (n = 2), and adenovirus (n = 4). M. smithii was detected in 47/49 (95.9%) specimens, no pathogen was detected in negative controls and S. enterica was identified in the S. enterica‐spiked positive control. The overall specificity was 100% and the overall sensitivity was 97.5% because one S. enterica sample was missed by the microarray. The multiplexed detection of C. jejuni spiked into an adenovirus‐positive stool sample gave positive results, with fluorescence values of 14.3 and 9.1, respectively. These data indicate that using the protocol developed in this article, the DNA array allows for the multiplexed detection of some enteropathogens in stool samples.